2006
DOI: 10.1002/dmrr.623
|View full text |Cite
|
Sign up to set email alerts
|

Metformin delays the manifestation of diabetes and vascular dysfunction in Goto–Kakizaki rats by reduction of mitochondrial oxidative stress

Abstract: These observations provide in vivo evidence that the generation of ROS plays an important role in the onset of diabetes and the development of vascular dysfunction in GK rats with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 46 publications
3
69
1
Order By: Relevance
“…Previous studies have shown similar findings that I/R leads to increased MDA and inactivation of antioxidant enzymes in rat testes 23,25,26 . ROS Metformin is a biguanide drug which improves the sensitivity to insulin, increases the insulin-stimulated uptake and utilization of glucose, reduces basal hepatic glucose production, causes weight reduction and decreases hunger 28 . Recent studies have recommended the use of this drug for kidney protection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown similar findings that I/R leads to increased MDA and inactivation of antioxidant enzymes in rat testes 23,25,26 . ROS Metformin is a biguanide drug which improves the sensitivity to insulin, increases the insulin-stimulated uptake and utilization of glucose, reduces basal hepatic glucose production, causes weight reduction and decreases hunger 28 . Recent studies have recommended the use of this drug for kidney protection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism underlying the increased production of ROS in the vasculature and the heart is still not completely understood, it has been proposed that the high rate of fatty acid oxidation increases mitochondrial membrane potential, which augments generation of ROS (2), and that overexpression of NAD(P)H oxidase isoforms (Nox-2 and Nox-4) in the vascular system and kidneys increases production of superoxide anion (O 2 Ϫ ) (13,22). It has also been demonstrated that O 2 Ϫ generated by Nox mediates oxidative damage to vascular tissue in diabetes (32,48,50).…”
Section: ϫ )] and The Mechanisms Underlying Omentioning
confidence: 99%
“…Although the mechanism underlying the increased production of ROS in the vasculature and the heart is still not completely understood, it has been proposed that the high rate of fatty acid oxidation increases mitochondrial membrane potential, which augments generation of ROS (2), and that overexpression of NAD(P)H oxidase isoforms (Nox-2 and Nox-4) in the vascular system and kidneys increases production of superoxide anion (O 2 Ϫ ) (13,22). It has also been demonstrated that O 2 Ϫ generated by Nox mediates oxidative damage to vascular tissue in diabetes (32,48,50).Under physiological conditions, constitutively active Nox produces low levels of O 2 Ϫ (28), which are removed by cellular antioxidants. However, under pathophysiological conditions protein kinase C (PKC)-dependent phosphorylation of p47 phox , a regulatory Nox subunit, leads to the activation of the enzyme following stimulation by factors such as angiotensin II, thrombin, and TNF-␣ (28, 31), thereby enhancing O 2 Ϫ generation.…”
mentioning
confidence: 99%
“…Many studies have shown that an altered vascular responsiveness characterized by increased reactivity to vasoconstrictors and impaired vasodilation exists in the diabetic state (13)(14)(15)(16)(17). We have demonstrated that chronic hyperinsulinemia in fructose-drinking rats, an experimental model for insulin resistance and type 2 diabetes, facilitates adrenergic nerve-mediated vasoconstriction, which is associated with attenuated CGRPergic nerve-mediated vasodilation (18).…”
Section: Introductionmentioning
confidence: 87%